Pengembangan Multimedia Interaktif Boga Dasar dengan Model Pengembangan 4D di SMK Negeri 3 Malang - Putu Ardian Pratama Putra; Isnandar; Syarif Suhartadi; Nila Rahmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This research is motivated by the lack of use of modern media in learning food material knowledge at SMK Negeri 3 Malang. Where previously it was only limited to the use of materials and PowerPoint. This study aims to develop interactive multimedia in Basic Culinary material at SMK Negeri 3 Malang using the 4D development model. This model consists of four stages, namely defining, designing, developing, and disseminating. This study uses a Research and Development (R&D) approach, with data collection through questionnaires given to teachers and students. The results of the development show that the developed interactive multimedia can improve students' understanding of the material, increase learning motivation, and enrich students' learning experiences. Validation by material, media, and learning design experts shows that this product is very suitable for use in the learning process. By using interactive multimedia, students can more easily understand the material and can learn independently. Based on the results of the study, it can be concluded that this interactive multimedia is effective in improving learning outcomes and student motivation in Basic Culinary subjects at SMK Negeri 3 Malang.